Pengembangan program inovatif PAAREDI dalam mewujudkan Transformasi Pendidikan Karakter Islami pada remaja melalui IBM Watson AI pada PKK Pariaman Timur - Mukhtar, Dertha; Prananda, Gingga (Universitas Muhammadiyah Magelang, 2025)
The problem formulation in this study is how to integrate technology, local wisdom, and Islamic character education to enhance the character development of teenagers in the challenging digital era. The aim of this research is to produce an educational product in the form of an effective and practical PAAREDI program model, to be implemented in the context of Islamic character education. The research method used is a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), consisting of five stages: analysis, design, development, implementation, and evaluation. The subjects of this study consist of 38 teenagers enrolled in PKK Pariaman Timur, who will participate as trial participants in the implementation of the PAAREDI program. The results of the study show that the PAAREDI program has a high level of validity, with expert validation reaching 96% for the material, 95% for the media, and 97% for the language of the module. The practicality test shows an increasing ease of implementation, with a score of 78.13% in the small-scale trial (fairly practical), 87.17% in the individual trial (practical), and 88.27% in the limited group trial (practical). The program's effectiveness evaluation shows that 85% of participants found it easier to understand Islamic character material after participating in the program, 80% felt that IBM Watson AI helped them understand the material in a personalized way, and 85% rated the PAAREDI module as easy to use and relevant for learning. Despite technical challenges such as limited internet access, this program has proven effective in enhancing understanding, motivation, and the application of Islamic character values. In conclusion, PAAREDI is an innovative learning model that integrates technology and local wisdom in Islamic character education, with great potential to be applied in various teenage communities in the digital era.